Corrigendum to “Enhancing corrosion resistance and bioactive behavior of porous metallic scaffolds through electrochemical coatings”(Applied Surface Science Advances, (2025), 26, C, (100723), (S2666523925000315),10.1016/j.apsadv.2025.100723) - de la Rosa, Julio E.; García-Cabezon, Cristina; García-Hernandez, Celia; Delgado-Pujol, Ernesto J.; García-García, Francisco J.; Boccaccini, Aldo R.; Martín-Pedrosa, Fernando; Torres, Yadir (Applied Surface Science Advances, 2025)
The authors regret one of the co-authors name in the article has been published incorrectly and it should be corrected from Bocaccini to Boccaccini. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2025-12-26